The Multi-Task Turning Test (The MTT Test) / Maria Justine … [et al.] - Justine, Maria; Daroi, Khairunnisa; Nordin, Nurhazwani; Alias, Hani Asilah; Manaf, Haidzir (Research Innovation Business Unit, 2014)
Turning is defined as the beginning and end of the 180-degree reversal of turn direction at one line while walking. Several characteristics can be described in turning activities such as time taken to accomplish the turn, the types of turn (step turn or pivot turn), and staggering during turn. A previous study also found that the steps and turning duration increased in individuals with balance dysfunction compared to individuals with normal balance. Based on this understanding, we developed an assessment tool known as The Multi-Task Turning Test (The MTT Test). The MTT test is a performance-based assessment tool designed to assess ability to perform a variety of single and dual-task turning. The concept of the MTT test was developed based on extensive literature. These tasks reflect activities of daily living such as walking and turning in the kitchen, toilet, and staircase. The MTT test can be used for hospitalized patients, older persons, as well as patients with neurological disorders such as stroke, Parkinson’s Syndrome, and Traumatic Brain Injury. These populations are known to have problems with turning ability that may put them at risk of falls. Similarly, the MTT test can also be used as part of a rehabilitation training. The validity of the MTT test has been evaluated for older persons by correlating it with the 10 meter walk test (10MWT) (gait speed) and the time-up and go (TUG) test (balance and agility). We also compared the MTT test between younger adults and older persons. Our analysis shows that some of the components in the MTT test were significantly correlated with the TUG test and 10MWT. In addition, the durations to complete the MTT test were significantly shorter in the younger adults. We conclude that the MTT test may be feasible for frail subjects. We also planned to refine the components of the MTT test in our future study. THE MULTI-TASK TURNING TEST (THE MTT TEST) Instruction: Please circle the appropriate score based on your observation of subject’s performance. The MTT Test Scoring Indicator: 0=Need minimal assistance to walk and stabilize 1=Able to walk and complete the task within 15 minutes or more 2=Able to walk and complete the task within 15 minutes and less Components 1. Walking forward turning i. Walk in 10 meter and turn back (0,1, 2) ii. Walk in 10 meter while holding a cup of water and turn back (0, 1, 2) 2. Step around obstacles i. Walking at normal speed until the first cone, walk around the right side of it, and until the second cone walk around to the left (0, 1, 2) ii. Walking at normal speed until the first cone, walk around the right side of it, and until the second cone walk around to the left while holding a cup of water (0, 1, 2) 3. Figure of 8 i. Walk on a figure of 8 (0, 1, 2) ii. Walk on a figure of 8 while holding a cup of water (0, 1, 2) 4. Pivot turning i. Turn 180 degree and walk 3 meter step forward (0, 1, 2) ii. Turn 180 degree and walk 3 meter forward while holding a cup of water (0, 1, 2) 5. Step climbing i. Climbing-up stairs, at the top, turn around, and walk down (0, 1, 2) ii. Climbing-up stairs, while holding a cup of water, at the top, turn around, and walk down (0, 1, 2)